Innovation Digital Literacy Public Administration In Indonesia: National Survey Data - Samudra, Dio; Tamamudin, Tamamudin; Ayatullah, Ayatullah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This research analyses the level of digital literacy in public administration in Indonesia through a systematic literature study approach. The study reviewed data from accredited journals from 2019-2024 with a focus on the relationship between digital literacy and public information disclosure. The results showed that 65.3% of users were still at a low to medium level, with significant gaps between basic operation skills (7.2/10) and advanced data analysis (3.4/10). There is a significant disparity between urban (6.8/10) and rural (4.2/10) communities in the understanding of digital information. Hypothesis testing confirmed strong relationships between digital literacy and data accessibility (r=0.783), public participation (β=0.534) and government accountability (β=0.623). Demographic analysis showed the 18-35 age group performed best (7.2/10), with a progressive decline in older age groups. Training programmes proved effective with a 72% increase in scores, despite infrastructure constraints. The study recommends the development of a standardised policy framework and continuous evaluation to address the digital divide. The implementation of AI showed a 38% increase in effectiveness, while the mobile approach improved accessibility by 65%. The findings confirm the important role of digital literacy in improving the effectiveness of public administration in Indonesia, although there are still gaps that need to be addressed through a comprehensive and sustainable approach.